Effect of microstructure on high cycle fatigue behavior of Ti–5Al–5Mo–5V–3Cr–1Zr titanium alloy. (January 2017) - Huang, Chaowen; Zhao, Yongqing; Xin, Shewei; Tan, Changsheng; Zhou, Wei; Li, Qian; Zeng, Weidong
Highlights: Both LM and BM present outstanding HCF strength, 652 MPa and 656 MPa, respectively. Prismatic slip lines, dislocation tangles and twins can be found in fatigued specimens. Microcracks mainly initiate at GB α films or at αs /βr interphases in LM. Microcracks primarily nucleate at αp /βtrans interfaces and at αp particles interiors in BM. Fatigue cracks growth with a rough path results from fine and local basket-weave αs lamellae. Abstract: High-cycle fatigue (HCF) behavior of Ti–5Al–5Mo–5V–3Cr–1Zr (Ti-55531) alloy with both lamellar microstructure (LM) and bimodal microstructure (BM) was studied at room temperature. The results indicate that BM presents much higher strength, lower ductility and slightly higher HCF strength (10 7 cycles, R = −1) than those of LM. Typical dislocation structures including straight prismatic slip lines, curved dislocation lines, dislocation tangles and twins can be discovered in fatigued specimens with two different microstructures. Primary α (αp ) particles and secondary α (αs ) lamellae accommodate more cyclic deformation than retained β (βr ) laths. Grain boundary (GB) α layers have more effect on promoting crack initiation in LM than that in BM. As a result, fatigue microcracks mainly initiate at the interface between GB α films and prior β grains or at the αs /βr interphase for LM. However, microcracks primarily nucleate at the αp /βtrans (β transformed microstructure) interface or at αp particles in BM. The combination of transgranular and intergranular crack propagation could be observed in the two microstructures. Crack front profile of macrocrack in LM is rougher than that of BM during the stable propagation region.